Investigation of The Fatty Acid Amounts in The Bee Pollens of Collected from Bingol’s Flora - Karagözoğlu, Yusuf; Parlak, Akif E.; Alayunt, Naci Ö. (Selçuk Üniversitesi, 2012)
In this study, fatty acid compounds in the bee pollens collected from five different locations of Bingöl were investigated. A total of 27 samples of polen, each 4 of which taken from 5 different places, were examined. Pollen samples were extracted and extractions were analyzed by gas choromatography (GC). According to results, while significant difference in the amount of palmitic acid (C16:0) and stearic acid (C18:0) oleic acid (C18:1n-9) and ? – linolenic acid (C18:3n-6) were found, the amounts of palmitoleic acid ( C16:1n-7), linoleic acid (C18:2n-6), ? – linolenic acid (C18:3n-3), saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) were not found significant (p>0.05). As a result, it was found that the unsaturated-to-saturated fatty acids ratio (TUFA/SFA ratio) in the pollen samples examined ranged from 1.57 to 1.92 and essential fatty acids appeared to be mixture of ?-linolenic acid and ?-linolenic acid, 33% and linoleic acid 10 %, respectively of the total fatty acids. It can be thought that with this study one can get information about biological value and nutritional quality of the pollen grains in the this region and this investigation will have an important effect on improvement of the knowledge of that area.

Bu çalışmada, Bingöl yöresinin beş farklı yerinden toplanan arı poleni örneklerindeki yağ asidi bileşenleri araştırıldı. Ça lışmada beş farklı yerin her birinden 4 örnek olmak üzere toplam 20 örnek kullanıldı. Polen örnekleri estraksiyon işlemi yapıldı ve ekstraksiyonlar gaz kromatografisiyle analiz edildi. Analiz sonuçlarına göre, palmitik asit (C16:0), stearik asit (C18:0), oleik asit (C18:1n-9) ve ? – linolenik asit (C18:3n-6) miktarlarında istatistiksel olarak anlamlı bir fark (p0.05). Sonuç olarak, polen örneklerindeki yağ asitlerinin doymamışlık oranının doymuşluğa oranına olan değerinin (TUFA/SFA) 1.57 - 1.92 arasında olduğu ve esansiyel yağ asitlerinden ? – linolenik asit ve ? – linolenik asit karışımının toplam yağ asitlerinin yaklaşık % 33’ü ve linoleik asitin toplam yağ asitlerinin yaklaşık % 10’u olduğu saptandı. Bu araştırmayla bölgedeki polenlerin biyolojik değeri ve besin kalitesi hakkında bilgi edinilebileceği ve bu araştırma sonuçlarının literatür bilgisine katkıda bulunabileceği düşünülmektedir
Bingöl Yöresinden Toplanan Arı Polenlerinin Yağ Asidi Miktarlarının İncelenmesi
Keywords: Agricultural Engineering (Other); Ziraat Mühendisliği (Diğer)